Resource Needs Assessment for Developing the Non- Textbook ‘Persahabatan Besi dan Magnet’ Based on the SDGs Framework in Junior High Schools - Wulan, Sinta Srie; Rubini, Bibin; Ardianto, Didit (Universitas Negeri Semarang, 2025)
This study assessed the resource needs for developing a non-textbook titled